Innovation of Automated Systems Used in Spreading Regulated Information by Issuers in the Republic of Bulgaria and the Social Effect Anticipated - Yavor Rusinov (Journal of Biomedical & Clinical Research)
This paper aims to demonstrate that improving automated systems used to spread regulated information has a positive social effect. The provision of capability to replace manual insertion, and particularly direct import of data in XML-format into the systems of information agencies will save time (“economization of time”) spent for spreading financial statements by 90%. The saved working time can be utilized to fulfill other office tasks within current employees’ obligations, carrying out office assignments not listed as present obligations. Employees could improve their qualification through familiarization with novelties in normative bases or with good practices of other companies, substitute colleagues absent from work (leave or sick leave), and analyze work environment and suggest improvements.